Polyposis and Oncologic Outcomes in Young-onset Sporadic Colorectal Cancer - Aday, Ulas (Euroasian J Hepatogastroenterol, 2021)
AIM: The present study aimed to investigate the effect of the presence of polyposis in sporadic early-onset colorectal cancer (EOCRC) on clinicopathological and oncological outcomes. METHODS: The retrospective study included patients with sporadic colorectal cancer aged 16 to 50 years who underwent curative resection at the general surgery clinics in two healthcare centers between 2013 and 2019. Patients were divided into two groups: polyposis and nonpolyposis. Clinicopathological characteristics and oncological outcomes were compared between the two groups. RESULTS: A total of 127 patients were included, of whom 60.6% were men. There were 25 (19.68%) patients in the polyposis group and 102 (80.31%) patients in the nonpolyposis group. Seventy-one (69.6%) of the nonpolyposis group and 23 (92.0%) of the polyposis group had adenocarcinoma histological types. The total number of patients with mucinous tumor and signet ring cell carcinoma in the nonpolyposis and polyposis groups was 31 (30.4%) and 2 (8.0%), respectively (p = 0.042). Five-year overall survival (OS) was 60 and 72% in the nonpolyposis and polyposis groups, respectively, and no significant difference was found (p = 0.332). In univariate analysis, American Joint Committee on Cancer (AJCC) tumor stage (pT) ≥3–4, lymph node positivity, presence of mucinous tumor and signet ring cell carcinoma, lymphovascular invasion, and advanced tumor-lymph nodesmetastasis (TNM) stage (III–IV) were found to be significant negative prognostic factors for OS, whereas none of these parameters were found to be prognostic factors in multivariate analysis. The presence of polyposis was not a significant factor on both univariate and multivariate analyses. CONCLUSION: Although the sporadic EOCRC cases developing on the basis of polyposis can have slightly better oncological outcomes, these outcomes are mostly similar to those of cases with nonpolyposis. HOW TO CITE THIS ARTICLE: Aday U, Kafadar MT, Oğuz A, et al. Polyposis and Oncologic Outcomes in Young-onset Sporadic Colorectal Cancer. Euroasian J Hepato-Gastroenterol 2021;11(1):6–10.